Functional community ecology meets restoration ecology: Assessing the restoration success of alluvial floodplain meadows with functional traits. Issue 3 (14th March 2016) - Engst, Karina; Baasch, Annett; Erfmeier, Alexandra; Jandt, Ute; May, Konstanze; Schmiede, Ralf; Bruelheide, Helge
Summary: Species‐rich grasslands are highly endangered habitats in Central Europe. To halt their ongoing loss, many sites have become subjects of restoration efforts. Traditionally, restoration success is measured using target species or by comparing similarity in species composition. Here, we suggest to additionally use functional community composition to assess restoration success as functional traits might offer mechanistic insights into restoration processes. In a 5‐year restoration experiment, we annually evaluated the responses of (i) floristic composition and species diversity, (ii) number and cover of target species, (iii) functional identity and (iv) functional diversity to four different methods of assisted recolonization through species introduction: hay transfer and application of threshing material from a local provenance, combined with and without addition of regional seed mixtures of target species, as well as to a control treatment. Across all treatments, floristic composition, species diversity, and number and cover of target species approached the values of reference sites. In the last observation year, Shannon diversity was still lower in all treatment plots than in the reference plots, while the number of target forb species had reached or exceeded the reference levels. We demonstrated that the community was also restored functionally in many aspects, but not in all studied traits. Calculated community‐weighted means (CWMs), specific leaf area (SLA) and leaf dry matter content (LDMC) in experimental plots did not differ significantly from the reference plots, thereby indicating that productivity of restored sites had reached target values. In contrast, CWMs of strategy types and pollination modes revealed significant differences, showing that biotic interactions among plant species and with other trophic levels have not yet been fully restored. However, almost all CWMs showed a trajectory towards the reference, thus giving a positive prospect for the future development. With respect to functional diversity (FD), we found steadily increasing FD values for almost all traits analysed. Synthesis and applications . We demonstrated that all applied restoration measures were appropriate to achieve the restoration aim in terms of species composition of a given community and the establishment of target species. With respect to many functional traits, the restored meadows were already as functional as communities from the reference sites. Hence, including functional criteria did not only corroborate traditional criteria of restoration success but also allowed identifying those floodplain meadow's functions that can be quickly and less quickly restored. Abstract : We demonstrated that all applied restoration measures were appropriate to achieve the restoration aim in terms of species composition of a given community and the establishment of target species. With respect to many functional traits, the restored meadows were already as functional as communities from the reference sites. Hence, including functional criteria did not only corroborate traditional criteria of restoration success but also allowed identifying those floodplain meadow's functions that can be quickly and less quickly restored.